Anatomical Analysis of the Unique Advantages of Tai Chi Exercise in Promoting Health - Song, Guangqing (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract:What is the unique health value of Tai Chi exercise? Can we explain the anatomical characteristics of Tai Chi compared to other sports from an anatomical perspective? Is Taijiquan exercise irreplaceable in promoting human health? With the above problems in mind, take the Twenty four Style Simplified Taijiquan as an example, and make a comparative analysis of the number of human links mobilized, the number of muscles mobilized, the angle of joint activities, and the speed of Muscle contraction, to find the key anatomical differences between Taijiquan and other sports. Provide anatomical evidence support for promoting human health through Tai Chi exercise.The study conducted anatomical comparative analysis between Tai Chi and other types of sports through methods such as comparative analysis and mathematical statistics. Other events include running and javelin in track and field, football and tennis in ball games, and Freestyle swimming in water sports. There are very unique differences in the movement trajectory and mode of the 24 style simplified Tai Chi compared to the above sports, mainly reflected in the following aspects. The first is the angle analysis of joint activities. The sum of the angles of Shoulder joint activities (flexion, extension, adduction, abduction, internal rotation, external rotation) is calculated. Taijiquan is significantly higher than the listed movements. Furthermore, from the perspective of joint movements such as elbow, knee, and hip joints, it can be further analyzed that Tai Chi is still higher than other sports. Secondly, analyze the balanced development of joints. Compared with simple running events, Tai Chi has a wider range of upper limb activities and a more balanced development of the upper and lower limbs. Compared with football, Tai Chi also has significant advantages in balancing upper and lower limb exercises. Compared to tennis and throwing events, Tai Chi has a more balanced development of the left and right upper limbs. Freestyle swimming is similar to Taijiquan in terms of limb balance. Thirdly, from the perspective of non repetitive skeletal muscle movement, excluding the influence of external forces, Tai Chi exercises have a higher number of skeletal muscle movements than other events. In the throwing event, the fixed movements of the dominant limb are constantly repeated, and the number of muscles mobilized is always around the joint of the throwing unilateral limb. The number of muscles mobilized in running is single and repetitive. The most commonly used forehand and backhand strokes and lower limb running in tennis are repetitive movements, while the foot ball also repeats a lot of movements in the process of running, shooting, and passing. Swimming and running are similar to one of the most repetitive movements. Fourthly, based on the analysis of skeletal muscle contraction speed, Tai Chi is the slowest among the listed items, with more pronounced centrifugal contraction of skeletal muscles and more support for far fixed movements. It has a combined effect on increasing the strength of skeletal muscles and protecting against muscle damage. Skeletal muscles contract faster in sprint events, and short-term contraction can cause significant damage to skeletal muscles. Marathons and other events have relatively slow contraction rates but high repeated contractions, which can also easily cause damage to skeletal muscles. Throwing events and tennis need to complete Muscle contraction to complete throwing and swing in 0.12-0.17 seconds. The slow contraction speed of skeletal muscles in swimming events is mainly due to resistance from water. The above four aspects provide a clear understanding of the unique anatomical perspective of Tai Chi, which in turn affects the different stimuli to human physiology.The different angles and activities of joints determine the range of limb activity. When each joint in the human body is limited by its basic material structure and reaches the limit of its normal range of activity through limb exercise, it conforms to the natural evolution laws of the human body and naturally brings corresponding promoting effects to human health. The balanced development of the human body is a fundamental condition for health. The phenomenon of a single joint significantly lagging behind other links in the human body will disrupt the overall balance of the body. For example, the uneven development of the lower limbs or left and right limbs is more likely to cause damage in sports such as strength and endurance, and differences in the number of capillaries and blood circulation efficiency will inevitably have an impact on other organs of the body. When some joints are exercised unevenly for a long time, they may be injured due to insufficient or excessive exercise. The number of skeletal muscles mobilized reflects the coordination ability of Sympathetic nervous system nerve, Parasympathetic nervous system nerve and autonomic nerve. When the number of muscles mobilized is just enough to complete the speed and angle required by the target action, the relevant movement is completed with the highest efficiency. It can be learned from the muscle silk sliding theory of skeletal muscle that the faster the Muscle contraction speed is, the greater the tension the thick muscle silk and the thin muscle silk bear, and the corresponding more subtle muscle silk damage will be generated. When enough coincidence is added, the damage will gradually accumulate to form a large area of damage after repeated enough times.An objective analysis and summary of the anatomy of Tai Chi movements found that compared to sports such as football, athletics, swimming, and tennis, the overall range of joint activity in Tai Chi is larger, the degree of balanced development of joints is higher, the number of non repetitive muscle movements is more, and the speed of skeletal muscle contraction is relatively slow. These anatomical features are precisely the advantages of Tai Chi in promoting health. Different anatomical movements lead to deeper physiological changes, and then further affect the coordination of various systems in the human body, ultimately promoting the maintenance and promotion of physical health. The unique advantages of Tai Chi in terms of its external form alone can be confirmed for human health, and the impact of Tai Chi on people’s internal thinking is also worthy of in-depth research. Compared with other sports, Tai Chi has the advantage of promoting health, starting from the form of external movements and then to the unity of spiritual form. The anatomical differences in external movements are a strong basis for its health promotion advantages.